EQUALITY IN THE ANIMATION WORKFORCE – HOW CLOSE ARE WE TO A GLOBALLY LEVEL PLAYING FIELD AND HOW CAN A NEW SCHOOL OF DIGITAL ARTS CONTRIBUTE TO PROGRESS? - Marshall, Kristin (Brazilian Creative Industries Journal, 2025)
This article looks to identify reasons behind a perceived lack of equality within the Animation workforce, if indeed this is still predominant in the Animation industry. It asks whether these gender gaps do still exist, continuing to compare the effect of gender equality issues within the sector and its work force, in relation to wider societal influences and comparisons. It will continue to make suggestion on the role educators should play in the continued promotion of equal opportunities to support all graduates, regardless of gender, ethnicity and social background and specifically how a new school, such as SODA, can lead in discussion to develop collaborative initiatives for continued future change.